Analisis Pengaruh Dana Alokasi Umum, Dana Alokasi Khusus dan PDRB Terhadap Tingkat Kemiskinan di Provinsi Sumatera Utara - Sihite, Karonika; Safuridar Safuridar; Nurlina Nurlina (Kajian Ekonomi dan Akuntansi Terapan, 2025)
This study aims to analyze the influence of the General Allocation Fund (DAU), the Special Allocation Fund (DAK), and the Gross Regional Domestic Product (GRDP) on the poverty rate in North Sumatra Province. The method used is multiple linear regression analysis using secondary data from 2004 to 2023. The results show that the DAU has a negative and significant effect on the poverty rate, meaning that the greater the DAU allocation, the lower the poverty rate in the province. Conversely, the DAK has a positive and significant effect on the poverty rate, indicating that an increase in DAK is actually followed by an increase in the poverty rate. Meanwhile, GRDP shows a negative effect on the poverty rate, but the effect is not significant. The coefficient of determination obtained shows that the DAU, DAK, and GRDP are able to explain variations in the poverty rate in North Sumatra Province. Simultaneously, the test results show that all three variables have a significant effect on the poverty rate. These findings suggest the importance of proper management of fund allocation and optimization of regional economic sectors to reduce poverty effectively.